Medicina defensiva: uma prática necessária? - Minossi, José Guilherme [UNESP]; Silva, Alcino Lazaro Da (Colégio Brasileiro de Cirurgiões, 2013)
We discuss the reasons why Defensive Medicine is widely used in Brazil and worldwide. The Defensive Medicine is characterized by excessive use of complementary tests, the use of supposedly safer therapeutic procedures, the frequent referral of patients to other specialists and by the refusal to care for critically ill patients and with greater potential for complications. This is a practice that aims to defend the doctor from legal suits. The way the processes are conducted by the judiciary certainly contributes to the consolidation of this foolish practice. The slow pace of justice in our country, associated with the unpreparedness of judges and legal experts in the analysis of cases, leads to an emotional exhaustion of the parties involved. Furthermore, poor training of doctors in our country values the use of sophisticated diagnostic and treatment methods, rather than a thorough clinical examination and appropriate communication with the patient. Besides inefficient in protecting the doctor, Defensive Medicine has severe consequences to the patient and to society, since it generates an additional invaluable cost to medical practice, determines greater suffering to the patient and causes deterioration of the doctor-patient relationship, which has always been marked by trust, respect and personhood.

O artigo em questão aborda os motivos pelos quais a Medicina Defensiva é largamente utilizada no Brasil e no Mundo. A Medicina Defensiva, na prática, se caracteriza pela utilização exagerada de exames complementares, pelo uso de procedimentos terapêuticos supostamente mais seguros, pelo encaminhamento frequente de pacientes a outros especialistas e pela recusa ao atendimento de pacientes graves e com maior potencial de complicações. Trata-se de uma prática que tem como objetivo principal defender o médico de eventuais processos, principalmente na área judicial. A maneira como são conduzidos os processos pelo poder judiciário certamente contribui para a consolidação desta prática insensata. A morosidade da justiça, em nosso meio, associado ao despreparo dos juízes e peritos judiciais na análise dos casos, leva a um desgaste emocional das partes. Alem disso, a formação precária do médico em nosso país faz com que se utilize de meios requintados de diagnóstico e tratamento em detrimento a um exame clínico pormenorizado e uma adequada comunicação com o paciente. Além de ineficiente em proteger o médico, a Medicina Defensiva traz consequências graves ao paciente e à sociedade, já que gera um custo adicional incalculável ao exercício da Medicina, determina um maior sofrimento ao doente e faz com que haja uma deteriorização na relação médico-paciente, que sempre foi pautada pela confiança, respeito e pessoalidade.
Defensive medicine: a necessary practice?
Keywords: Medicina defensiva; Procedimentos clínicos; Prática profissional; Erros médicos; Prova pericial; Defensive medicine; Critical care; Professional practice; Medical errors; Expert testiony